Molecular cloning of cDNA encoding the Xenopus homolog of mammalian RelB. - Suzuki, K (1995)
We have molecularly cloned cDNA encoding a new Rel-related protein in Xenopus laevis. Nucleotide sequencing revealed that the product is most homologous to mammalian RelB in its N-terminal region. Furthermore, the putative protein kinase A phosphorylation site (RRPS), found in most of the Rel family proteins, but replaced by QRLT in mammalian RelB, is replaced by QRIT, indicating that our cDNA most likely encodes the Xenopus homolog of mammalian RelB (XrelB). As in the case of mouse RelB, XrelB alone does not bind to DNA efficiently, while XrelB/human p50 heterodimers bind to kappa B sites and activate transcription. XrelB transcripts are present at all stages of oocyte maturation and in adult tissues examined. However, in staged embryos XrelB is undetectable from neurula to stage 28 and resumes expression at stage 47, while Xrel1/XrelA, the Xenopus homolog of p65, has been demonstrated to be expressed throughout embryogenesis. These results raise the possibility that XrelB and Xrel1/XrelA play different roles in the development of X.laevis.